Silymarin Protects Against Acute Ethanol-Induced Hepatotoxicity in Mice - Song, Zhenyuan (2006)
BACKGROUND: Accumulated evidence has demonstrated that both oxidative stress and abnormal cytokine production, especially tumor necrosis factor-α (TNF), play important etiological roles in the pathogenesis of alcoholic liver disease (ALD). Agents that have both antioxidant and anti-inflammation properties, particularly anti-TNF production, represent promising therapeutic interventions for ALD. We investigated the effects and the possible mechanism(s) of silymarin on liver injury induced by acute ethanol (EtOH) administration. METHODS: Nine-week-old mice were divided into 4 groups, control, silymarin treatment, EtOH treatment, and silymarin/EtOH treatment, with 6 mice in each group. Because control and silymarin values were virtually identical, only control treatment is shown for ease of viewing. Ethanol-treated mice received EtOH [5 g/kg body weight (BW)] by gavage every 12 hours for a total of 3 doses. Control mice received an isocalorical maltose solution. In the silymarin/EtOH group, silymarin was dissolved in the EtOH and gavaged simultaneously with EtOH at a dose of 200 mg/kg BW. At 4 hours after the last dosing, the mice were anesthetized and subsequent serum alanine aminotransferase (ALT) level, hepatic lipid peroxidation, enzymatic activity of hepatic cytochrome P450 2E1, hepatic TNF-α, and glutathione (GSH) levels were measured. Histopathological change was assessed by hematoxylin and eosin staining. RESULTS: Acute EtOH administration caused prominent hepatic microvesicular steatosis with mild necrosis and an elevation of serum ALT activity, induced a significant decrease in hepatic GSH in conjunction with enhanced lipid peroxidation, and increased hepatic TNF production. Supplementation with a standardized silymarin attenuated these adverse changes induced by acute EtOH administration. CONCLUSIONS: Silymarin protects against the liver injury caused by acute EtOH administration. In view of its nontoxic nature, it may be developed as an effective therapeutic agent for alcohol-induced liver disease by its antioxidative stress and anti-inflammatory features.